Coefficient Estimates for Some Classes of Biunivalent Function Associated with Jackson q-Difference Operator. (9th September 2022) - Ali, Ekram E.; Lashin, Abdel Moneim; Albalahi, Abeer M.
Abstract : Using the Jackson q -difference operator, we present two new subclasses of biunivalent functions. Furthermore, we estimate the initial Taylor-Maclaurin coefficients a 2 and a 3 of functions belonging to these new subclasses. Our results generalize some of the previously related works of several authors.